PERAN FATWA DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA (Ahkam: Jurnal Hukum Islam, 2023)
This study aims to determine the Role of Fatwas in Forming Legislation in Indonesia. This research is a library research with a normative and conceptual theology approach. The results of this research show that the ulema's fatwa is the result of a configuration of Islamic law formulations. The fatwa is the result of the ijtihad of a mufti who is related to the issues or problems presented to him. The fatwa of the Ulama is usually an appeal from a group of Ulama and sometimes it is an appeal from certain Ulama to the general public or certain communities. The results of Islamic scholars' fatwas in Indonesia, nationally, are set forth in the form of MUI (Indonesian Ulema Council) fatwas. History since the founding of the MUI until now, there have been many MUI fatwas and advice as products of Islamic legal thought absorbed in various laws and regulations.